Nama Sebagai Sebuah Kesadaran Identitas Manusia Sunda: Kajian Budaya - Isnendes, Retty (LOKABASA, 2020)
A person's self name refers to the language used by his parents in attaching identity to his child. Language is one of the elements of culture which is very dominant and the opening of a culture. The identity of one's ethnic group will be seen from the ethnic language or region used and one of them, which is attached to oneself as an individual trait. The identity of the name as a Sundanese human characteristic also reflects the region of space and time awareness in addressing itself as part of a tribe in a global vortex. Maintaining self-name by carrying out Sundanese culture in the midst of the temptation of global cultural gatherings is difficult if parents do not have awareness about national identity. The names that are attached to the child become an indication in measuring his consciousness as a Sundanese. In this article the question concerning the names of students of the Sundanese Language Education Department is raised in the culture studies.AbstrakNama diri seseorang berkenaan dengan bahasa yang dipakai orang tuanya dalam melekatkan identitas pada diri anaknya. Bahasa merupakan salah satu unsur budaya yang sangat dominan dan pembuka satu kebudayaan. Identitas suku bangsa seseorang akan terlihat dari bahasa etnis atau daerah yang dipakainya dan salah satunya, yang dilekatkan pada diri sebagai ciri individu. Identitas nama sebagai ciri manusia Sunda juga mencerminkan wilayah kesadaran ruang dan waktu dalam menyikapi dirinya sebagai bagian dari sebuah suku bangsa dalam pusaran global. Mempertahankan nama diri dengan mengusung budaya Sunda di tengah godaan pertemuan budaya global merupakan hal berat bila orang tua tidak punya kesadaran mengenai jati diri bangsa. Nama-nama yang dilekatkannya pada anak menjadi indikasi tersendiri dalam mengukur kesadarannya sebagai manusia Sunda. Dalam artikel ini diketengahkan persoalan mengenai: nama diri mahasiswa di Departemen Pendidikan Bahasa Sunda dalam kajian budaya.Â